2001
DOI: 10.1002/j.1556-6978.2001.tb01267.x
|View full text |Cite
|
Sign up to set email alerts
|

Examining Supervisor Impairment From the Counselor Trainee's Perspective

Abstract: Although there is a growing body of literature on counselor impairment, the topic of supervisor impairment has surprisingly been overlooked. The author explores the implications of working with an impaired supervisor at various levels of counselor development and discusses some of the critical factors that may influence how a supervisee decides to handle this problem. In addition to discussing the misuse of power by the impaired supervisor, other factors (e.g., the nature and severity of the supervisor's impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Nevertheless, Cobia and Pipes suggested supervisors take on mandated supervision cases with great caution, given the lack of empirical support and potential legal risks. Muratori (2001) examined another difficulty situation: supervisees who believe they are working with an impaired supervisor. Muratori discussed the range of impairments (e.g., burnout, substance abuse, sexual exploitation) and emphasized that assessing the nature and severity of the impairment is key to determining an appropriate course of action.…”
Section: Supervision In Counseling: Interdisciplinary Issues and Resementioning
confidence: 99%
“…Nevertheless, Cobia and Pipes suggested supervisors take on mandated supervision cases with great caution, given the lack of empirical support and potential legal risks. Muratori (2001) examined another difficulty situation: supervisees who believe they are working with an impaired supervisor. Muratori discussed the range of impairments (e.g., burnout, substance abuse, sexual exploitation) and emphasized that assessing the nature and severity of the impairment is key to determining an appropriate course of action.…”
Section: Supervision In Counseling: Interdisciplinary Issues and Resementioning
confidence: 99%
“…These standards for the conduct of psychotherapy as well as methods of supervision must be clear. The components of such a contract have been reviewed elsewhere (Bordin, 1983; Muratori, 2001).…”
Section: Applying Kernberg's Hierarchy Of Thematic Prioritiesmentioning
confidence: 99%
“…At the most basic level, therapist deviation from the agreed-upon framework creates a readily observable phenomenon that can be a part of the development of supervision themes. While it is much less frequently discussed and bears much more work, supervisor impairment can be a threat to the functionality of the supervisory relationship (Muratori, 2001). This is an area that can be particularly difficult because of the supervisor's investment in her/his role as well as the extent to which the supervisee may legitimately depend on the mentorship and professional support of the supervisor.…”
Section: Threats To Supervision Continuitymentioning
confidence: 99%
“…The recognition of the impact impaired health care professionals have on the community has been extensively researched (Briton & Rapisarda, 2007; Muratori, 2001), and licensing has been identified as an effective mechanism to deal with such individuals. A study conducted at the Menninger Clinic concluded that “Licensing and regulatory agencies can take proactive steps to identify professionals with social and emotional vulnerabilities who may be at greater risk for unethical and negligent behavior” (2004).…”
Section: Rule Making In Licensing Boards and The Impaired Professionalmentioning
confidence: 99%